Level of knowledge of students in the fifth year of veterinary medicine in a private university in Concepcion, Chile, about major zoonotic diseases transmitted by dogs and cats - Luzio Q., Luzio Q. (2015)
This study aimed to determine the level of knowledge of students in the fifth year of Veterinary Medicine at the University of Santo Tomas, Concepción, Chile in relation to the most common zoonoses in the country. A questionnaire on general knowledge, etiology, epidemiology, transmission and prevention-control of zoonoses transmitted by dogs and cats was applied. The questionnaire had 90 multiple-choice questions with four distractors and only one correct answer, and the results were grouped in five levels: very good, good, fair, bad and very bad. The results showed that 85% of students scored between 55 and 72 from a maximum of 90 points. The best performance was obtained for etiology (55% were in the level of very good) and the poorest in the category of transmission (50% in the level of fair). Ir was concluded that the students had an adequate knowledge of prevalent zoonotic diseases in the country, especially on etiology.